2013
DOI: 10.2478/v10247-012-0076-9
|View full text |Cite
|
Sign up to set email alerts
|

Physical properties and compression loading behaviour of corn seed

Abstract: A b s t r a c t. The aim of this study was to acquire data on the physical properties and compression loading behaviour of seed of six corn hybrid varieties. The mean values of length, width, thickness, geometric diameter, surface area, porosity, single kernel mass, sphericity, bulk and true density, 1 000 kernel mass and coefficient of friction were studied at single level of corn seed moisture content. The calculated secant modulus of elasticity during compressive loading for dent corn was 0.995 times that o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 12 publications
3
35
1
3
Order By: Relevance
“…There were significant differences in the BR between the half‐dent and dent maize ( p < .01). The data for the averaged BR showed that the half‐dent hybrids had stronger damage resistance than the dent hybrids; this is in agreement with the study by Babić et al, who found that the secant modulus of elasticity for dent maize hybrids was 0.995 times that of half‐dent maize hybrids (Babić et al, ). The elastic modulus is a measure of a material's resistance to elastic deformation.…”
Section: Resultssupporting
confidence: 90%
“…There were significant differences in the BR between the half‐dent and dent maize ( p < .01). The data for the averaged BR showed that the half‐dent hybrids had stronger damage resistance than the dent hybrids; this is in agreement with the study by Babić et al, who found that the secant modulus of elasticity for dent maize hybrids was 0.995 times that of half‐dent maize hybrids (Babić et al, ). The elastic modulus is a measure of a material's resistance to elastic deformation.…”
Section: Resultssupporting
confidence: 90%
“…They have reported physical and mechanical properties of seeds, nuts, kernels and fruits such as maize (BartPlange et al), arigo seeds (Davies, 2010), tef seed (Ozarslan), chick pea, wheat grains (Aydin, 2002) (Ixtaina et al, 2008), rice (Correa et al, 2007), raw and parboiled paddy (Reddy & Chakraverty, 2004), and hemp seeds (Sacilik et al, 2003; flaxseed (Singh et al, 2012) and corn seed (Babic et al, 2013). Despite these efforts little has been done on the physical properties of BBG seeds talkless of developing simple empirical models for the relationships between these aforementioned properties and moisture content that may cause significant change in their magnitude.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have studied the mechanical properties of various agricultural materials such as corn seed (Babic et al, 2013), soybean (Bargale et al, 1999), white sesame seed (Darvishi, 2012), and maize (Barnwal et al, 2012). Joshi (1993) observed that the force required to initiate seed coat rupture of pumpkin seed increased as moisture content increased from 5.1 to 10.5% d.b., beyond which it steadily decreased up to a moisture content of 21.7% d.b.…”
Section: Introductionmentioning
confidence: 99%